The Association Between Arterial Stiffness and Muscle Indices Among Healthy Subjects and Subjects With Cardiovascular Risk Factors: An Evidence-Based Review - Aminuddin, Amilia; Noor Hashim, Muhammad Fakhrurrazi; Mohd Zaberi, Nur Aina Syazana; Zheng Wei, Lee; Ching Chu, Beh; Jamaludin, Nur Amalina; Salamt, Norizam; Che Roos, Nur Aishah; Ugusman, Azizah (Frontiers in Physiology, 2021)
Low muscle mass and muscle function was associated with increased risk of cardiovascular disease (CVD). This may be mediated by increased arterial stiffness (AS). Therefore, the focus of this review was to investigate the correlation between AS and muscle indices. Three databases were used to search for relevant studies. These keywords were used: “arterial stiffness” OR “vascular stiffness” OR “aortic stiffness” OR “pulse wave velocity” OR “carotid femoral pulse wave velocity” OR “pulse wave analysis” AND “muscle” OR “skeletal” OR “flexibility” OR “range of motion” OR “articular” OR “arthrometry” OR “strength” OR “hand strength” OR “pinch strength” OR “mass” OR “lean” OR “body composition”. The criteria were; (1) original articles, (2) full articles were available, (3) articles in English language, (4) articles that reported the correlation between AS measured as cfPWV or baPWV and muscle indices measured as muscle mass, muscle flexibility and muscle strength, and (5) human study. The search identified 2295 articles published between 1971 and June 2021. Only 35 articles fulfilled the criteria and mostly involved middle and old age subjects. Fourteen out of 19 studies found that there were significant inverse correlation between muscle strength and PWV (Pearson r ranged from -0.14 to -0.693, P<0.05). Fifteen out of 17 studies found that PWV was correlated with muscle mass (with Pearson r ranged from -0.11 to -0.589, P<0.05). For the association between muscle flexibility and arterial stiffness, three out of four studies found that PWV was significantly correlated with sit-and-reach test (Pearson r ranged from -0.16 to -0.670, P<0.05). In conclusion, there is a significant inverse correlation between muscle indices and AS. AS could be the factor that links poor muscle indices with future CVD. However, most of the studies involved middle age and older subjects while studies among the young are lacking. Future studies should focus on this issue.